The effect of an intramedullary implant with a static magnetic field on the healing of the osteotomised rabbit femur - (:unkn) unknown (SPRINGER, 2011)
Static magnetic fields are a type of electromagnetic fields used in clinical practice. To ascertain what effect a static magnetic intramedullary device implanted in the rabbit femur had on fracture healing, 20 male New Zealand white rabbits with magnetic/nonmagnetic intramedullary implants were examined histologically, radiologically and for bone mineral density. Three groups were constituted according to the poles of the magnets. During surgery the intramedullary device was driven into the medulla. A femoral osteotomy was created with a mini Gigli wire at the centre point of the rod. Radiographs were obtained at the second and fourth weeks. Histological examination and bone mineral density were evaluated at the fourth week. The results of this study verified that an intramedullary implant with a static magnetic field improves bone healing in the first two weeks radiologically and that the configuration difference in magnetic poles has an effect on bone quality. Static magnetic fields have minor effects on bone mineral density values.
Keywords: PULSING ELECTROMAGNETIC-FIELDS; BONE-FORMATION; NON-UNION; FRACTURES; RADIUS